Preparation method of hollow fiber microporous membrane and hollow fiber microporous membrane
By adopting a cast film liquid preparation method with high molecular weight polyvinylidene fluoride and mixed ionic liquid diluent, combining nanoclay and polyethylene glycol 6000 to optimize the structure, the VOCs emission problem in the preparation process of PVDF hollow fiber microporous membrane was solved, and efficient VOCs treatment and environmentally friendly production were achieved.
Patent Information
- Application Number
- CN202510793078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-08-08
- Estimated Expiration
- 2045-06-13
AI Technical Summary
The existing PVDF hollow fiber microporous membranes have VOCs emission problems during the preparation process, which affects the environment and health, and the use of dibutyl phthalate as a diluent limits its application in VOCs treatment.
A cast film liquid was prepared by 800,000 weight-average molecular weight polyvinylidene fluoride and mixed ionic liquid diluents 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide salt and choline acetate combined with Sipan 80. The hollow fiber microporous membrane was prepared by spinneret extrusion, cooling, extraction and drying to avoid VOCs emissions, and the membrane structure was optimized through nanoclay and polyethylene glycol 6000.
The prepared hollow fiber microporous membrane maintains high throughput, has high mechanical strength and low mass transfer resistance, significantly improving the separation efficiency of VOCs, and achieving a green and environmentally friendly production process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of separation, and more specifically, to a method for preparing a hollow fiber microporous membrane and the hollow fiber microporous membrane. Background Art
[0002] VOCs, or volatile organic compounds, are a major source of environmental pollution. Gas separation membrane technology is a simple, energy-efficient, and environmentally friendly method for VOC control. By efficiently separating and recovering VOCs using gas separation membranes, it can significantly improve VOC control effectiveness.
[0003] Polyvinylidene fluoride (PVDF) has excellent thermal stability, chemical resistance and easy processing into membranes. It has been widely used in microfiltration, ultrafiltration, membrane bioreactors, membrane distillation, gas separation, removal of pollutants in water, biofuel collection, lithium-ion battery separators and ion exchange membranes. It is also a common membrane material for VOCs gas separation membranes.
[0004] Thermally Induced Phase Separation (TIPS) is a novel microporous membrane preparation technology. Its principle is to form a homogeneous solution of thermoplastic and semi-crystalline polymers with certain high-boiling-point small molecule diluents at high temperatures. Upon cooling, factors such as solubility and polymer crystallization induce liquid-liquid (LL) or solid-liquid (SL) phase separation, forming polymer-rich and polymer-lean phases. After the diluent is extracted, a microporous structure is formed in the space occupied by the diluent. Due to the good repeatability of the TIPS membrane formation process and the high precision of membrane pore structure control, this method is now widely used to prepare PVDF hollow fiber microporous membranes.
[0005] When preparing PVDF hollow fiber microporous membranes using the TIPS method, the choice of diluent is crucial. It determines the polymer crystallization process and the final membrane morphology, thereby affecting membrane properties such as pore size, strength, and flux. Dibutyl phthalate (DBP) is widely used in the preparation of PVDF membranes, but it is a high-VOC substance that is easily released into the environment, posing potential hazards to human health and the environment. As a result, the preparation process of PVDF hollow fiber microporous membranes is not low-VOC, and its use in VOC remediation is significantly limited. Summary of the Invention
[0006] In order to maintain the high flux of the hollow fiber microporous membrane while reducing the VOCs emission during the preparation process of the hollow fiber microporous membrane, the present application provides a preparation method of the hollow fiber microporous membrane and the hollow fiber microporous membrane.
[0007] In a first aspect, the present application provides a method for preparing a hollow fiber microporous membrane, which adopts the following technical solution: A method for preparing a hollow fiber microporous membrane comprises the following steps: Preparation of a casting solution: The casting solution comprises the following raw materials in parts by weight: 30-40 parts of polyvinylidene fluoride, 70-75 parts of a diluent, and 0.4-0.6 parts of Span 80. The raw materials are mixed and vacuum degassed to prepare the casting solution. The polyvinylidene fluoride has a weight-average molecular weight of 800,000. The diluent comprises 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and choline acetate in a weight ratio of 17:3. Extrusion molding: With the diluent as the core liquid, the casting liquid is extruded through a spinneret, and then cooled, wound, extracted and dried to obtain a hollow fiber microporous membrane.
[0008] The above technical solution, utilizing polyvinylidene fluoride (PVDF) with a weight-average molecular weight of 800,000, provides the membrane with high breaking strength, capable of withstanding the high-pressure impact and organic solvent corrosion associated with VOC treatment. The diluent utilizes a mixed ionic liquid, a combination of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and choline acetate. The 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (containing the TFSI⁻ anion) provides high thermal stability, ensuring the membrane's structural stability during high-temperature exhaust gas treatment. It also directs the dissolution of PVDF, inhibits hydrolysis, and improves solvent stability. Choline acetate enhances biodegradability, reduces toxicity, lowers the viscosity of the mixed system, accelerates phase separation, and forms a uniform sponge layer. The resulting membrane structure, formed by combining the two as diluents, features interconnected sponge-like pores, enhancing the mass transfer pathway for VOCs during subsequent membrane applications. This significantly reduces mass transfer resistance, increases flux, and thus improves separation efficiency. It also significantly improves the membrane's mechanical strength. The preparation process also eliminates VOC emissions, making it a truly green and efficient process. Span 80 can eliminate surface pinholes, reduce membrane pore defects, and improve the membrane's processing efficiency. Therefore, it can maintain the high flux of the hollow fiber microporous membrane while reducing VOCs emissions during the preparation process of the hollow fiber microporous membrane.
[0009] Optionally, the casting solution further comprises 2 to 4 parts by weight of polyethylene glycol 6000 and 5 to 7 parts by weight of nanoclay.
[0010] By employing this technical solution, nanoclay is incorporated into the high-molecular-weight polyvinylidene fluoride matrix. The combination of the two can improve membrane strength. Polyethylene glycol 6000 promotes the formation of an open-pore structure in the membrane, increasing porosity, while the nanoclay compensates for the decrease in membrane strength caused by the increased porosity. The combination of the two optimizes the membrane pore structure and improves pore uniformity. Furthermore, since oils and particulates in VOCs can easily clog membrane pores, polyethylene glycol 6000 can reduce contamination caused by hydrophobic adsorption.
[0011] Optionally, the casting solution further comprises 1 to 3 parts by weight of polyvinyl pyrrolidone and 2 to 4 parts by weight of lithium chloride.
[0012] By adopting the above technical solutions, the combination of the two can synergistically improve the hydrophilicity of the membrane, enhance anti-pollution properties, reduce oil adsorption, thereby increasing flux and improving separation efficiency.
[0013] Optionally, the casting solution further comprises 4 to 6 parts by weight of ZIF-8.
[0014] By adopting the above technical solution, ZIF-8 has a microporous structure. Doping ZIF-8 can enhance the membrane's screening ability to handle the separation of complex components. At the same time, PVP can effectively inhibit the agglomeration of ZIF-8, and nanoclay can compensate for the strength loss caused by the addition of ZIF-8. The combination of these multiple raw materials forms a high-strength, high-throughput green hollow fiber microporous membrane.
[0015] Optionally, the extrusion flow rate of the casting liquid is 10 mL / min; the core liquid flow rate is 4 mL / min.
[0016] Optionally, during cooling, the cooling temperature is 15° C., the coolant is deionized water, and the cooling rate is 25° C. / min.
[0017] Optionally, the extraction includes ethanol primary extraction and supercritical CO2 secondary extraction.
[0018] By adopting the above technical solution, the residual diluent can be completely removed.
[0019] In a second aspect, the present application provides a hollow fiber microporous membrane, which adopts the following technical solution: A hollow fiber microporous membrane is prepared by the above-mentioned hollow fiber microporous membrane preparation method.
[0020] By adopting the above technical solution, the prepared hollow fiber microporous membrane can maintain high flux while reducing VOCs emissions during the preparation process.
[0021] In summary, this application has the following beneficial effects: 1. Since this application uses polyvinylidene fluoride with a weight-average molecular weight of 800,000, the membrane has a high breaking strength and can withstand high-pressure impact and organic solvent corrosion in VOCs treatment. The diluent uses a mixed ionic liquid diluent, and the membrane structure formed has a through sponge-like pore, which enhances the mass transfer path of VOCs during subsequent membrane applications, significantly reduces mass transfer resistance, and increases flux, thereby improving separation efficiency. It also has a significant effect on improving the mechanical strength of the membrane. There is no VOCs emission in the preparation process, which is truly green and efficient. Span 80 can eliminate surface pinholes, reduce membrane pore defects, and improve the treatment efficiency of the membrane. Therefore, it is possible to achieve the effect of reducing VOCs emissions in the preparation process of the hollow fiber microporous membrane while maintaining the high flux of the hollow fiber microporous membrane.
[0022] 2. In this application, PEG6000 and nanoclay are preferably used. Nanoclay enters the high molecular weight polyvinylidene fluoride matrix. The combination of the two can improve the membrane strength; polyethylene glycol 6000 can promote the formation of an open-pore structure in the membrane and increase the porosity, and nanoclay can compensate for the decrease in membrane strength caused by the increase in porosity. The combination of the two can optimize the membrane pore structure and improve the uniformity of pore formation.
[0023] 3. The hollow fiber microporous membrane prepared by the method of the present application can maintain high flux while reducing VOCs emissions during the preparation process. DETAILED DESCRIPTION
[0024] The present application is further described in detail with reference to the following examples. It is particularly noted that, in the following examples, if no specific conditions are specified, conventional conditions or conditions recommended by the manufacturer are followed, and the raw materials used in the following examples are all commercially available unless otherwise specified.
[0025] 1-Ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [EMIM]TFSI, CAS: 174899-82-2.
[0026] Nanoclay was purchased from Beishi Zongheng Science Company and was surface modified. The manufacturer was Sigma, with the product number 682632 and the MDL number MFCD00147658.
[0027] Choline acetate, CAS number: 14586-35-7.
[0028] ZIF-8, CAS No. 59061-53-9, was purchased from Xi'an Qiyue Biological.
[0029] Example
[0030] Example 1 A method for preparing a hollow fiber microporous membrane comprises the following steps: Preparation of casting solution: The casting solution includes the following raw materials: polyvinylidene fluoride, diluent, and Span 80. The amount of each raw material is shown in Table 1.
[0031] The weight average molecular weight of polyvinylidene fluoride is 800,000, and it was vacuum dried at 80°C for 12 hours before use to remove moisture.
[0032] The diluent comprises 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and choline acetate in a weight ratio of 17:3, which are uniformly mixed and dehydrated at 120° C. under vacuum for 48 hours before use to reduce the moisture content to ≤50 ppm.
[0033] Under an inert atmosphere, polyvinylidene fluoride was dissolved in a diluent and stirred at 180°C for 3 hours to completely dissolve the polyvinylidene fluoride. Then, Span 80 was added and mixed evenly. Vacuum degassing was performed at -0.1 MPa to obtain a casting solution.
[0034] Extrusion molding: The casting solution was extruded through a spinneret with a diluent as the core liquid. The spinneret dimensions were 1.2 mm inner diameter and 2.5 mm outer diameter. The spinning temperature was 175°C for the barrel and 180°C for the spinneret. The casting solution extrusion rate was 10 mL / min, and the core liquid flow rate was 4 mL / min. The membrane was then cooled and quenched in a 15°C deionized water bath at a cooling rate of 25°C / min. The membrane was then wound with an air section height of 20 cm and a winding speed of 10 m / min. Extraction was then performed by soaking in anhydrous ethanol at 70°C for 12 hours for primary extraction, followed by washing with supercritical CO2 at 40°C and 20 MPa for secondary extraction. Finally, critical point drying (CPD) was performed to obtain a hollow fiber microporous membrane.
[0035] A hollow fiber microporous membrane is prepared by the above preparation method.
[0036] Example 2 The difference between this embodiment and embodiment 1 is that the amounts of the raw materials used are different, see Table 1 for details.
[0037] Example 3 The difference between this embodiment and embodiment 1 is that the amounts of the raw materials used are different, see Table 1 for details.
[0038] Example 4 This example differs from Example 2 in that the casting solution further includes polyethylene glycol 6000 (PEG6000) and nanoclay, with the amounts used being shown in Table 1. The polyethylene glycol 6000 was dried at 80°C for 6 hours before use. The nanoclay was surface-modified with silane.
[0039] The preparation method of the casting solution is: Under an inert atmosphere, polyvinylidene fluoride was dissolved in a diluent and stirred at 180°C for 3 hours to completely dissolve the polyvinylidene fluoride. Polyethylene glycol 6000, nanoclay, and Span 80 were then added sequentially. The mixture was stirred at high shear (2000 rpm) for 30 minutes to mix thoroughly. Vacuum degassing was performed at -0.1 MPa to prepare a casting solution.
[0040] Example 5 The difference between this embodiment and embodiment 4 is that the amounts of polyethylene glycol 6000 and nanoclay are different, see Table 1 for details.
[0041] Example 6 The difference between this embodiment and embodiment 4 is that the amounts of polyethylene glycol 6000 and nanoclay are different, see Table 1 for details.
[0042] Example 7 The difference between this embodiment and embodiment 5 is that this embodiment does not contain polyethylene glycol 6000.
[0043] Example 8 The difference between this embodiment and embodiment 5 is that this embodiment does not contain nanoclay.
[0044] Example 9 The difference between this embodiment and embodiment 5 is that the casting solution further includes polyvinyl pyrrolidone (PVP, K30) and lithium chloride, and the amounts used are shown in Table 1. The polyvinyl pyrrolidone and lithium chloride were dried at 80° C. for 6 h before use.
[0045] The preparation method of the casting solution is: Under an inert atmosphere, polyvinylidene fluoride was dissolved in a diluent and stirred at 180°C for 3 hours to completely dissolve the polyvinylidene fluoride. Then, polyethylene glycol 6000, polyvinyl pyrrolidone, lithium chloride, nanoclay, and Span 80 were added in sequence. The mixture was stirred at high shear speed (2000 rpm) for 30 minutes to mix thoroughly. Vacuum degassing was performed at -0.1 MPa to prepare a casting solution.
[0046] Example 10 The difference between this embodiment and embodiment 9 is that the amounts of polyvinyl pyrrolidone and lithium chloride used are different, see Table 1 for details.
[0047] Example 11 The difference between this embodiment and embodiment 9 is that the amounts of polyvinyl pyrrolidone and lithium chloride used are different, see Table 1 for details.
[0048] Example 12 The difference between this embodiment and embodiment 10 is that this embodiment does not contain polyvinyl pyrrolidone.
[0049] Example 13 The difference between this embodiment and embodiment 10 is that this embodiment does not contain lithium chloride.
[0050] Example 14 The difference between this embodiment and embodiment 10 is that the casting solution further includes ZIF-8, and the amount used is shown in Table 1.
[0051] The preparation method of the casting solution is: Under an inert atmosphere, polyvinylidene fluoride was dissolved in a diluent and stirred at 180°C for 3 hours to completely dissolve the polyvinylidene fluoride. Polyethylene glycol 6000, polyvinyl pyrrolidone, lithium chloride, and nanoclay were then added in sequence. Zinc oxide (ZIF-8) and Span 80 were added below 60°C. High-speed shear (2000 rpm) stirring was used for 10 minutes to initially disperse the ZIF-8. Ultrasonic treatment (200 W, 5 minutes) was then performed to homogenize the mixture. Vacuum degassing was performed at -0.1 MPa to prepare the casting solution.
[0052] Example 15 The difference between this embodiment and embodiment 14 is that the amount of ZIF-8 used is different, see Table 1 for details.
[0053] Example 16 The difference between this embodiment and embodiment 14 is that the amount of ZIF-8 used is different, see Table 1 for details.
[0054] Comparative Example Comparative Example 1 A method for preparing a vinylidene fluoride hollow fiber membrane: (1) Add normal molecular weight polyvinylidene fluoride (weight average molecular weight 330,000) / diluent (dibutyl phthalate) into the reactor at a mass ratio of 26 / 74, mix and stir at 160°C for 3 hours, and then vacuum degas for 3 hours to obtain a uniform casting solution.
[0055] (2) A diluent (dibutyl phthalate) was used as the core liquid, the core liquid temperature was 80°C, the core liquid flow rate was 0.03 L / min, and the casting liquid was measured by a spinning pump and continuously extruded from the hollow fiber spinneret at a flow rate of 0.05 L / min. After passing through an air gap of 0.5 cm, it was immersed in a 25°C coagulation bath (deionized water) to cool and form. The membrane filaments were then immersed in anhydrous ethanol for 48 hours to extract the residual diluent in the membrane, and then immersed in deionized water for 24 hours to remove the residual ethanol. Finally, the membrane filaments were naturally dried to obtain polyvinylidene fluoride hollow fiber membranes.
[0056] A polyvinylidene fluoride hollow fiber membrane is prepared by the above preparation method.
[0057] Comparative Example 2 The difference between this comparative example and Example 2 is that the weight average molecular weight of the polyvinylidene fluoride in this comparative example is 330,000.
[0058] Comparative Example 3 The difference between this comparative example and Example 2 is that the diluent in this comparative example is dibutyl phthalate.
[0059] Comparative Example 4 The difference between this comparative example and Example 2 is that the diluent in this comparative example is 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt.
[0060] Comparative Example 5 The difference between this comparative example and Example 2 is that the diluent in this comparative example is choline acetate.
[0061] Comparative Example 6 The difference between this comparative example and Example 2 is that there is no Span 80 in this comparative example.
[0062] Table 1 Types and amounts of raw materials for casting solutions in various examples and comparative examples
[0063] Performance testing Detection method 1. Determination of porosity: The average pore size and porosity of the membranes of the above embodiments and comparative examples were measured by mercury intrusion porosimetry. Each membrane was tested five times and the average value was taken. The results are shown in Table 2.
[0064] 2. Pure water flux test: After sealing and casting, a 300 mm membrane filament was tested with 25°C pure water at a pressure of 0.1 MPa for 2 hours. The pure water flux per unit area and time was then calculated. The average value of the five tests was taken. The results are shown in Table 2.
[0065] 3. Breaking strength test: A 100 mm fiber membrane was subjected to a tensile test on a universal testing machine at a linear speed of 10 mm / s. The maximum force at which the membrane filament broke was recorded and the breaking strength was measured. The test was repeated five times and the average value was taken. The results are shown in Table 2.
[0066] 4. Contact Angle Measurement: The contact angle of the film was measured using a contact angle meter (DSA100). A drop of water (1 μm) was dropped onto the film using a needle. The measurement was repeated three times, and the average value was taken as the contact angle. The results are shown in Table 2. The lower the contact angle, the stronger the surface film's anti-fouling properties.
[0067] Table 2 Test results
[0068] In combination with Example 2 and Comparative Examples 1 to 6, the preparation method of the hollow fiber microporous membrane of the present application does not use high-VOCs raw materials in the preparation process, uses mixed ionic liquid as a diluent, and no VOCs are emitted during the preparation process, achieving green production. In combination with Table 2, it can be seen that the prepared hollow fiber microporous membrane has high flux and high strength, and the pore structure is suitable for VOCs treatment.
[0069] Principle of Analysis: During membrane preparation, the casting solution uses polyvinylidene fluoride (PVDF) with a weight-average molecular weight of 800,000, resulting in a membrane with high breaking strength, capable of withstanding the high pressure shock and organic solvent corrosion associated with VOC treatment. The diluent is a mixed ionic liquid, a combination of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and choline acetate. 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (containing the TFSI⁻ anion) provides high thermal stability, ensuring the membrane's structural stability during high-temperature exhaust gas treatment. It also directs the dissolution of PVDF, inhibits hydrolysis, and improves solvent stability. Choline acetate enhances biodegradability, reduces toxicity, lowers the viscosity of the mixed system, accelerates phase separation, and forms a uniform sponge layer. The resulting membrane structure, formed by combining these two diluents, possesses interconnected sponge-like pores, enhancing the mass transfer pathway for VOCs during subsequent membrane applications. This significantly reduces mass transfer resistance, increases flux, and thus improves separation efficiency. It also significantly enhances the membrane's mechanical strength. The preparation process is VOC-free, making it a truly green and efficient process. Span 80 can eliminate surface pinholes, reduce membrane pore defects, and improve the membrane's processing efficiency. Therefore, it can maintain the high flux of the hollow fiber microporous membrane while reducing VOCs emissions during the preparation process of the hollow fiber microporous membrane.
[0070] In combination with Example 2 and Example 5 and in combination with Table 2, it can be seen that PEG6000 and nanoclay are added to the casting solution, and nanoclay enters the high molecular weight polyvinylidene fluoride matrix, and the combination of the two can bring about an increase in membrane strength; Polyethylene glycol 6000 can cause the membrane to form an open-pore structure, thereby improving porosity, and nanoclay can make up for the decrease in membrane strength caused by the increase in porosity. The combination of the two can optimize the membrane pore structure and improve pore uniformity. In addition, the grease or particulate matter in VOCs easily clogs the membrane pores, and polyethylene glycol 6000 can reduce the pollution caused by hydrophobic adsorption. In combination with Examples 7 and 8 and in combination with Table 2, it can be seen that when PEG6000 and nanoclay are compounded, the effect is best.
[0071] Combining Examples 5 and 10 with Table 2, it can be seen that the addition of PVP and lithium chloride to the casting solution can synergistically improve the hydrophilicity of the membrane, enhance anti-fouling properties, and reduce oil adsorption, thereby increasing flux and improving separation efficiency. Combining Examples 12 and 13 with Table 2, it can be seen that the best effect is achieved when PVP and lithium chloride are combined.
[0072] Combining Examples 10 and 16 with Table 2, we can see that the addition of ZIF-8 to the casting solution, due to its nanoporous structure, effectively handles the separation of complex components, such as toluene. This makes the membrane more suitable for VOCs treatment and significantly improves the membrane's separation efficiency.
[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A method for preparing a hollow fiber microporous membrane, characterized in that: The following steps are involved: Preparation of a casting solution: The casting solution comprises the following raw materials in parts by weight: 30-40 parts of polyvinylidene fluoride, 70-75 parts of a diluent, and 0.4-0.6 parts of Span 80. The raw materials are mixed and vacuum degassed to prepare the casting solution. The polyvinylidene fluoride has a weight-average molecular weight of 800,000. The diluent comprises 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and choline acetate in a weight ratio of 17:
3. Extrusion molding: With the diluent as the core liquid, the casting liquid is extruded through a spinneret, and then cooled, wound, extracted and dried to obtain a hollow fiber microporous membrane.
2. The method for preparing a hollow fiber microporous membrane according to claim 1, wherein: The casting solution further comprises 2 to 4 parts by weight of polyethylene glycol 6000 and 5 to 7 parts by weight of nano clay.
3. The method for preparing a hollow fiber microporous membrane according to claim 2, wherein: The casting solution further comprises 1 to 3 parts by weight of polyvinyl pyrrolidone and 2 to 4 parts by weight of lithium chloride.
4. The method for preparing a hollow fiber microporous membrane according to claim 3, wherein: The casting solution further comprises 4 to 6 parts by weight of ZIF-8.
5. The method for preparing a hollow fiber microporous membrane according to claim 1, wherein: The extrusion flow rate of the casting liquid is 10 mL / min; the core liquid flow rate is 4 mL / min.
6. The method for preparing a hollow fiber microporous membrane according to claim 1, wherein: During cooling, the cooling temperature is 15°C, the cooling liquid is deionized water, and the cooling rate is 25°C / min.
7. The method for preparing a hollow fiber microporous membrane according to claim 1, wherein: The extraction process includes ethanol primary extraction and supercritical CO2 secondary extraction.
8. A hollow fiber microporous membrane prepared by the method for preparing a hollow fiber microporous membrane according to any one of claims 1 to 7.
Citation Information
Patent Citations
PVDF hollow fiber membrane material used for hemodialysis and having anticoagulation characteristic, and preparation method thereof
CN110743392A
Separation method of ion liquid
JP2015096255A
Method for Manufacturing Hollw fiber Membrane
KR1020100116257A
Preparation of layer-by-layer materials and coatings from ionic liquids
US20120156389A1
Cited By
Hollow fiber membrane for decomposing refractory organic matters and preparation method of hollow fiber membrane
CN121466825A